Osteonecrosis Of Femoral Head—Overview, Current Management And Treatment Strategies (Texas Journal of Medical Science, 2024)
Osteonecrosis (ON) is a severe disabling disease that often develops in young people of working age and is associated with the death of bone cells in a certain area of bone tissue, usually caused by a disruption of the local blood supply. ON most often develops in the head of the femur. Factors that can provoke the development of ON of the head of the femur include traumatic injury to the hip joint, surgical interventions on it, dysplasia of the hip joints, immune-inflammatory rheumatic diseases, various coagulopathies, hyperlipidemia, genetic abnormalities, chronic liver diseases, treatment with glucocorticoids (GC), radiation and polychemotherapy, alcohol abuse and a number of others. According to the literature, among the pathogenetic factors associated with COVID-19 and causing bone destruction, there are coagulopathy, endothelial dysfunction and endotheliitis, hyperproduction of cytokines, activation of the complement system, thrombotic microangiopathy, hypoxia and a number of other mechanisms, including the direct damaging effect of the virus on trabecular and cortical bone tissue. The article presents our own clinical observation describing a case of ON development after a new coronavirus infection. Thus, all individuals who have had COVID-19, regardless of the severity of the coronavirus infection and the use or lack of use of GC, should be considered vulnerable to the development of ON and should be included in the risk group for this complication